The Detection and Analysis of Factors Associated with the Incidence of Lumpy Skin Disease in Cattle Transhipped at Merak Port, Indonesia - Rafiq, Faizal; Murtini, Sri; Mujiatun, Mujiatun; Dewi, Arum Kusnila; Adiningsih, Melani Wahyu (Jurnal Medik Veteriner, 2025)
Lumpy Skin Disease (LSD) is caused by the Lumpy Skin Disease Virus (LSDV) that affects cattle and buffalo. The symptoms include the development of lumps or nodules on the skin of infected animals. Therefore, this study aimed to detect the presence of LSD and determine factors associated with the incidence in cattle transhipped through Merak Port. Samples were collected in the form of oral and nasal swabs, then tested with quantitative real-time PCR (qPCR). The results showed that there were two positive LSD samples confirmed by molecular testing using qPCR. The positive cattle did not show clinical signs or were suspected to be sub-clinically infected, while the Ct values obtained were 27.71 and 28.88. The use of molecular methods with qPCR showed relatively good results for the detection of LSD. Cattle that did not show clinical signs were detected as positive by the test. This is because qPCR can detect viruses more quickly and accurately, even at very low viral load levels. Factors associated with the incidence of LSD in the Merak Port (p < 0.05) were farm origin and biosecurity measures, knowledge of livestock handlers, vaccination status, and disinfection practices.